Ecosystem drivers of an Arctic fox population at the western fringe of the Eurasian Arctic - Ims, Rolf Anker; Killengreen, Siw Turid; Ehrich, Dorothee; Flagstad, Øystein; Hamel, Sandra; Henden, John-André; Jensvoll, Ingrid; Yoccoz, Nigel Gilles (Polar Research, 2017)
Source at http://doi.org/10.1080/17518369.2017.1323621 The distribution of traditional breeding dens on the Varanger Peninsula (70–71°N) in northernmost Fennoscandia indicates that this area once harboured a large Arctic fox population. Early 20th century naturalists regarded the coastal tundra of the Fennoscandian Low Arctic to be a stronghold for the species. At the start of our research in 2004, however, the local Arctic fox population was critically small and most neighbouring populations had been extirpated. Here, we synthesize the results of 11 years of research to highlight ecosystem drivers behind the critical state of the Arctic fox in Low-Arctic Fennoscandia. We identify two fundamental drivers: (1) an increasingly climate-driven irregularity of the lemming cycle and (2) a management- and climate-driven increase in the abundance of red fox that is subsidized by more ungulate carrion. Arctic fox reproductive success is low when lemmings are scarce (despite high vole abundance), while red foxes exclude Arctic foxes from high-quality breeding territories in summer and from marine and terrestrial carrion in winter. Red fox culling on Varanger Peninsula may have prevented the extirpation of the Arctic fox population. However, one decade after the onset of this management action the Arctic fox population has failed to increase either because the action has been insufficient or because demographic and environmental stochasticity has precluded a positive response. We discuss options for future research and management of the Arctic fox in the Fennoscandian Low Arctic.